Hubungan Motivasi Mahasiswa Pada Praktek Laboratorium Asuhan Kegawatdaruratan Maternal dan Neonatal (KGD) dengan Hasil Belajar Asuhan Kegawatdaruratan Maternal dan Neonatal (KGD) Pada Mahasiswa Semester IV Di Akademi Kebidanan Ibt.isam Aulia Kisaran Tahu - Eliza Bestari Sinaga (Universitas Prima Indonesia, 2019)
Abstract learnig outcomes are to find out the extent to with students have been able to learn from certain subjects by conducting evaluations ,competencies in the form knowledge ,skill,and attitude periodically in the form of midterm formative, semester. the study aims to determaine the relationship of students motivation in laboratory practices with learning outcomes of maternal and neonatal emergency care ( KGD ) in semester IV students .this type of research is a descriptive analytic study using cross sectional design . the population was fourth semester students of ibtisam aulia midwifery kisaran 2018/2019 school year which consisted of 1 class totaling 25 peoples.the sample in this study is the total population data analysis was univariate ,analysis and bivariete analysis with chi square test. the results showed that there was a significant relationship between motivation in KGD laboratory practices and KGD care learning outcomes .its recommended to increase guidance on improving maternal and neonatal emergency care learning outcomes ( KGD )